Study of the granulation tissue of the adventitia of an old hydatic cyst of the liver operated - Lasnier, E. P.; Ardao, H. A.; Cassinelli, J. F. (Cirugía del Uruguay, 2020)
Presented in Session of July 24th, 1946.